Metodologia de projeto eletrotérmico de LEDs aplicada ao desenvolvimento de sistemas de iluminação pública - Bender, Vitor Cristiano (2012)
This work presents an LED electrothermal design methodology applied to a street lighting system. The methodology aims to provide indicatives of the optimal LED operating point for lighting systems design, considering electrical, thermal and photometric system features. Different projects are developed according to the methodology, the theoretical results are compared with fluid dynamics simulation and demonstrated by experimental results. A research including luminous flux, luminous efficacy and flicker is performed considering the LED current ripple, defining acceptable levels of ripple based on the optimal operational point. The methodology is applied by developing a lighting system composed of an LED driver and a thermal dissipation system, comprising a luminaire, a heatsink and fans. The lighting system includes electrothermal feedback control. The results provide high power factor with low current harmonic distortion to the power grid. The LED operational temperature ensures the luminous flux maintenance over the system lifetime.